Embryo developmental disruption during organogenesis produced by CF-1 murine periconceptional alcohol consumption - Coll, Tamara Anahí (2011)
The aim was to study the control females (CF)-1 mouse embryo differentiation, growth, morphology on embryonic E- and N-cadherin expression at midgestation after periconceptional moderate alcohol ingestion. Adult female mice were exposed to 10% ethanol in drinking water for 17 days previous to and up to day 10 of gestation (ethanol-exposed females, EF) and were compared with nonexposed CF. EF presented reduced quantities of E10 to E10.5 embryos, greater percentage of embryos at stages less than E7.5, reduced implantation site numbers/female, and increased resorptions compared with CF. EF-embryo growth was significantly affected as evidenced by reduced cephalic and body sizes of E10 and E10.5 embryos (scanning electron microscopy) and decreased protein content of E10.5 embryos vs. CF embryos. A significantly higher percentage of EF-E10-10.5 embryos presented abnormal neural tube (NT) closure vs. the percentage of CF. E10 embryos from EF presented elevated tissue disorganization, pyknosis and nuclear condensation in somites, mesenchymal and neuroepithelial tissue. Immunohistochemical E- and N-cadherin distribution patterns were similar in organic structures of E10 embryos between groups. However, western blot revealed that E- and N-cadherin expression levels were significantly increased in EF-derived embryos vs. controls. Perigestational ethanol consumption by CF-1 mice induced significant damage in the organogenic embryogenesis by producing delayed differentiation, growth deficiencies, and increasing the frequency of NT defects. Ethanol exposure may disrupt cell–cell adhesion leading to upregulation of E- and N-cadherin expression suggesting that deregulation of cell adhesion molecules could be involved in the disruption of embryo development at organogenesis in CF-1 mouse.